Riociguat treatment for portopulmonary hypertension: a subgroup analysis from the PATENT‐1/‐2 studies. (1st May 2018) - Cartin‐Ceba, Rodrigo; Halank, Michael; Ghofrani, Hossein‐Ardeschir; Humbert, Marc; Mattson, John; Fritsch, Arno; Krowka, Michael
Abstract : In patients with portopulmonary hypertension (n = 13) included in the 12‐week randomized placebo‐controlled PATENT‐1 trial, riociguat was well tolerated and improved 6‐min walking distance (6MWD), World Health Organization functional class (WHO FC), and other efficacy parameters; 6MWD and WHO FC improvements were sustained over two years in the open‐label extension, PATENT‐2.